2018
DOI: 10.1002/pmh.1413
|View full text |Cite
|
Sign up to set email alerts
|

Exploring electrophysiological correlates of social cognition in subclinical schizotypy

Abstract: Impairments in social cognition and associated abnormalities in brain function are well documented in psychotic disorders. They may represent neurodevelopmental vulnerabilities and may therefore be present in less severe or even subclinical conditions of the schizophrenia spectrum, such as schizotypy. Schizotypy has features highly suggestive of social cognitive impairments, but little is known about possible related abnormalities of brain function. This exploratory pilot study examines electrophysiological ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Of note, a few studies in the general population have also reported an association between reduced P300 amplitudes and schizotypal features (Davidson et al, 2018;Deng et al, 2023;Klein et al, 1999), which may reflect a genetic vulnerability for psychosis (e.g., Lenzenweger, 2018).…”
Section: Family Studies Of P300mentioning
confidence: 99%
“…Of note, a few studies in the general population have also reported an association between reduced P300 amplitudes and schizotypal features (Davidson et al, 2018;Deng et al, 2023;Klein et al, 1999), which may reflect a genetic vulnerability for psychosis (e.g., Lenzenweger, 2018).…”
Section: Family Studies Of P300mentioning
confidence: 99%